Strategies for exploring electrostatic and nonelectrostatic contributions to the interaction of helical antimicrobial peptides with model membranes - Alvares, D. S. [UNESP]; dos Santos Cabrera, M. P. [UNESP]; Ruggiero Neto, J. [UNESP] (Elsevier, 2016)
Linear antimicrobial peptides, short sequences up to 50 amino acids, rich in basic and hydrophobic residues, are able to form an amphipathic helix when adsorbed onto lipid membranes. Thanks to these characteristics they may impose perturbation on the lipid packing that can result in the lysis of the cell. The adsorption is mainly driven by electrostatic interactions due to their positive net charge and anionic lipid head groups in the membrane, or even charge-dipole and short-range interactions in the case of zwitterionic membranes. In the coupled adsorption and folding processes, the electrostatic and hydrophobic energetic contributions are mandatory. These contributions to the energy of the interaction are not additives and other contributions are important in the energetic balance. Here, we revisit the experimental techniques that allowed assessing the electrostatic and nonelectrostatic contributions to the adsorption to lipid bilayers, taking an example an alpha-helical antimicrobial peptide with acidic and basic residues. We explore the application of Langmuir isotherms obtained from fluorescence and circular dichroism experiments, of ζ-potential measurements and the Gouy- Chapman theory; and the peptide impact on the lipid packing investigated by Langmuir monolayers.